DEVELOPMENT OF A FIVE-TIER DIAGNOSTIC TEST TO IDENTIFY STUDENTS’ MISCONCEPTIONS ON ELASTICITY AND HOOKE’S LAW - Wibisana, Syifa Salsabila; Maison, Maison; Falani, Ilham (Universitas Tanjungpura, 2026)
This study aims to diagnose students' conceptions and identify their sources related to elasticity and Hooke's law using a five-level multirepresentation diagnostic instrument. A quantitative method with a research and development design was used involving 33 eleventh-grade students from SMA Negeri 13 Jambi City. Data were collected through a 15-question multirepresentation test, interviews, and documentation. Validity and reliability analysis using SPSS showed that the instrument was reliable (Cronbach's Alpha = 0.911). The implementation of this research instrument showed that the average percentage of students' correct answers (at Levels 1-4) was only 19.9%, indicating low conceptual understanding. Then, this study also identified students' misconceptions, which included 14 main types of misconceptions with an overall average percentage (at Levels 1-4) of 13.6%, which is also categorized as low. Personal thinking was identified as the main source of misconceptions, providing important insights for designing physics learning interventions. The uniqueness of this study lies in the application of a five-level diagnostic instrument to identify misconceptions and their sources, by finding that students' thinking is the main source. The results of this study provide important implications for physics education, including targeted intervention strategies and increased conceptual clarity, which ultimately support the teaching and learning of basic physics concepts.